Differences in the Students’ Perceptions on the Teaching of Neuroanatomy in a Medical Curriculum Organized by Disciplines and an Integrated Medical Curriculum - Arantes, Mavilde (2017)
Introduction: On the subject of curriculum reform, most European medical schools are moving away from an educational approach consisting of discipline-based courses to an integrated curriculum. The aim of this study was to compare, in the Faculty of Medicine of the University of Porto, Portugal, the teaching of neuroanatomy in a medical curriculum organized by disciplines and in an integrated medical curriculum.Material and Methods: Two hundred sixty one students who completed the Curricular Unit with a discipline-based approach (Neuroanatomy) and 202 students who completed it with an integrated approach (Morphophysiology of the Nervous System) were asked to complete a questionnaire on their perceptions about the Curricular Unit.Results: Our study showed that students of the Curricular Unit with a discipline-based approach had higher grades and evaluated it higher than students who followed the integrated approach. However, it also showed that students’ grades had a significant effect on the evaluation of the curricular unit, with students with higher grades evaluating higher than students with lower grades. Besides, the majority of the students of the Curricular Unit with an integrated approach appreciated this curriculum model and highlighted as a positive point the successful integration of contents covered in the three components of the curricular unit.Discussion: The curriculum reform led to the integration of neuroanatomy with other disciplines and resulted in a reduction of the teaching hours, a redefinition of the syllabus contents and the students’ learning objectives, the introduction of new educational methods and changes in the evaluation system.Conclusion: Our study could not prove conclusively the supremacy of one pedagogic approach to neuroanatomy over the other. Future initiatives to explore different pedagogical models in medical education are needed and should be of major concern to the medical faculty.